IMPROVING OF STUDENTS MATHEMATICAL REASONING ABILITY BY APPLYING REALISTIC MATHEMATICS EDUCATION ON APPROACH SUBJECT SETS IN VII GRADESMP NEGERI 1 BINJAI - Rully Sulistiowati; Hasratuddin Hasratuddin (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2016)
The aim of this research is to improve students’ mathematics  reasoning in class VII SMP Negeri 1 Binjai in Sets topic by using realistic mathematic education. Subject on this research is students in class VII-7 SMP which total students is 36 students and object this research is process and learning outcomes in improvement of mathematic reasoning ability through realistic mathematic education. Instrument of this research are observation, interview, and test. This research is Class Action Research (CAR) which is divided into 2 cycles, This research had done in two cycles which each cycle had two meetings and the end of each meeting was given mathematical reasoning ability test.from cycle I, the average score of mathematics reasoning test I 67,90 and there are 24 students of 36 students individually accomplished and classically mastery learning is 67%, this shows that students’ reasoning ability still low. In implementation of cycle II from score of mathematic reasoning test II got the average score of mathematic reasoning test II is 75,16 and classically mastery learning has achieved 89% or 32 students has completed the learning individually. Based on this research result is obtained that learning by using realistic mathematic education in the topic of sets can improve students’ mathematic reasoning. Based on criteria of classical mastery learning then this learning has achieved the target of mastery learning. The improvement can be concluded that through realistic learning, the mathematic reasoning ability in sets topic in class VII has improved. The suggestion which is recommended that teacher able to implemented the realistic mathematic education as alternative in learning process which can improve the students reasoning ability.